2010
DOI: 10.1590/s1413-81232010000200030
|View full text |Cite
|
Sign up to set email alerts
|

Transtornos alimentares na visão de meninas adolescentes de Florianópolis: uma abordagem fenomenológica

Abstract: Transtornos alimentares na visão de meninas adolescentes de Florianópolis: uma abordagem fenomenológicaEating disorders in the view of teenage girls from Florianópolis, Santa Catarina State: a phenomenological approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…Negative feelings associated with binge-eating episodes, such as loss of control, sadness, shame, anguish, anger, guilty and self-punishment were also observed in the study by McNamara et al 27 and Nunes & Vasconcelos 8 , and according to Appolinário & Claudino 36 it is common that binge-eating episodes occur when the individual is hidden, because of these negative feelings.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Negative feelings associated with binge-eating episodes, such as loss of control, sadness, shame, anguish, anger, guilty and self-punishment were also observed in the study by McNamara et al 27 and Nunes & Vasconcelos 8 , and according to Appolinário & Claudino 36 it is common that binge-eating episodes occur when the individual is hidden, because of these negative feelings.…”
Section: Discussionmentioning
confidence: 70%
“…Food restriction, irregular meal patterns, aversion to some macronutrients, prohibition of certain foods, fear of eating certain foods and food rituals are characteristic examples of eating behaviors in patients with anorexia nervosa 5,6,7,8 . Binge eating episodes, characterized by eating a larger amount of food than normal within two hours with a feeling of loss of control, may also be present 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex process that permeates social interactions; it influences health, and it is a source of pleasure, but also of anxiety and fear 5 . Nunes and Vasconcelos 28 observed that for patients with AN food represented torture, terror, fear and decadence. Moreover, they reported it as being a drug, an obligation, something that takes their freedom away.…”
Section: Importance Of Foodmentioning
confidence: 99%
“…O culto ao corpo perfeito está associado a uma imagem social de beleza e poder; contudo, muitas vezes os padrões estéticos são quase inalcançáveis, sendo crescente a insatisfação das pessoas com sua própria aparência (ALMEIDA et al, 2005;MACEDO et al, 2015). Esse padrão distorcido de beleza atinge principalmente indivíduos do gênero feminino que se submetem a dietas restritivas, excesso de exercícios físicos, uso indiscriminado de laxantes, diuréticos e drogas anorexígenas, comportamentos considerados como precursores de transtornos alimentares (SAIKALI et al, 2004;CARVALHO;AMARAL;FERREIRA, 2009;NUNES;VASCONCELOS, 2010).…”
Section: Introductionunclassified